IDENTIFICATION OF BIOACTIVE COMPONENTS IN ENHALUS ACOROIDES SEAGRASS EXTRACT BY GAS CHROMATOGRAPHYâ€“MASS SPECTROMETRY - P, Amudha; M, Jayalakshmi; N, Pushpabharathi; V, Vanitha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study deals with the determination of possible phytocompounds present in the ethyl acetate extract of Enhalus acoroides using gas chromatography-mass spectroscopy (GC-MS) technique. Methods: Using GC-MS technique the phytocompounds present in the ethyl acetate extract of E. acoroides whole seagrass was investigated, and the mass spectra of the compounds found in the extract were matched with the National Institute of Standards and Technology library. Results: GC-MS analysis of E. acoroides extract revealed the existence of several phytocompounds which includes 1-nonadecene (17.15%), n-tetracosanol-1 (11.48%), 1-octadecene (10.06%), 2-pentadecanone (7.87%), behenyl alcohol (7.33%), 17-pentatriacontene (4.84%), triacontane (4.25%), tetratetracontane (4.17%), and butylated hydroxytoluene (2.09%). Conclusion: E. acoroides possess distinct phytocompounds such as 1-nonadecene and n-tetracosanol-1 which possess antioxidant property, triacontane which has antibacterial, antidiabetic and antitumor activities. Further studies need to elute novel bioactive compounds and toxicity profile through animal models. Â 